Towards a conceptual framework for developing capabilities of 'new' types of students participating in higher education in Sub-Saharan Africa. (March 2016) - Tumuheki, Peace Buhwamatsiko; Zeelen, Jacques; Openjuru, George Ladaah
Highlights: NTS' participation in education is affected by factors from within the institution. NTS' participation in education is also affected by factors outside the institution. Some non-institutional participation factors are context specific. Key for SSA context is collectivism, non-informal labour markets and social norms. Capability approach presents the best framework for participation realities in SSA. Abstract: Building on the participation model of Schuetze and Slowey, this study contributes to the public discourse on theoretical considerations for guidance of empirical research on participation of non-traditional students (NTS) in higher education in Sub-Saharan Africa (SSA). Drawing from empirical work at Makerere University Uganda, we found that improving only the institution environment cannot suffice as there are also other factors affecting participation outside the institutional structures. These include family and work environments and context specific factors like perceptions and socio-cultural environment of the Ugandan society. A conceptual model specific to SSA is thus proposed, and the capability approach presented as the most insightful in elucidating the participation realities of NTS in SSA.